A critical review on phytosynthesis of gold nanoparticles: Issues, challenges and future perspectives. (1st August 2021) - Ahmad, Tausif; Iqbal, Jibran; Bustam, Mohamad Azmi; Irfan, Muhammad; Anwaar Asghar, Hafiz Muhammad
Abstract: The ecological, economical, and operational drawbacks associated with chemical, physical, and microbial modes, employed for the synthesis of gold nanoparticles (AuNPs) are the major stumbling blocks, which have confined their progressively growing industrial and medical applications. In this context, plants and their parts including leaves, flowers, steams, seeds, roots and biowastes have shown their untapped potential for the cost-effective, renewable, and eco-friendly synthesis of AuNPs. This review is majorly focused on the plant resources, explored for the phytosynthesis of AuNPs along with their as-developed surface features, detection of reactive biomolecules acting as reducing and stabilizing agents, reaction mechanism, impact of process parameters and quantitative evaluation of their growth kinetics. A critical analysis on identification of bioactive compounds in plant extracts has confirmed the key roles of phenolic compounds, flavonoids, proteins and terpenoids in the bioreduction of gold ions and biostabilization of AuNPs, explained through several reported hypothetical reaction mechanisms. The reaction period (2 min–4 days), concentration (0.2–4.055 mM) and volume of gold precursor (1.0–25 mL), reaction temperature (20–100 °C), volume of plant extract (0.2–20.0 mL) and pH of reaction mixture (2–14.0) revealed their decisive roles in forming size, morphology, and stability of as-developed AuNPs. The predicted growth kinetics of phytosynthesized AuNPs using Ostwald ripening and Orientation attachment models were found in agreement with experimental size evolution over a period of time. This review is written with an intention to unfold the key research challenges and future directions associated with phytosynthesis of AuNPs such as identification of reactive phytochemicals, reaction conditions and mathematical estimation of growth kinetics, which may be useful for their tuneable surface features-based phytofabrication. Graphical abstract: Image 1